Error Analysis in Short Dialogue Using Future Tense - Putri Erito, Silvia Nanda (Applied Research on English Education (AREE), 2023)
Error analysis plays an important role in investigating errors in the acquisition of a second or foreign language. This error analysis is part of the investigation into the process of learning English. The research aimed of this study is to analyze the types of errors made by the students of SMAN 2 Semarang on writing future tense sentences in a short dialogue. In this research, the researchers will discuss the types of interlingual errors. Qualitative descriptive methods used to find the types of errors that made by the students. The data was gathered through written task in the form of students’ writing short dialogue in  English using future tense. The Findings showed that the researchers found a non-contrastive analysis which was divided into 4 such as, over-generalization, ignorance of rules restrictions, incomplete application of rules, and hypothesized false concepts. As a result of student work, based on the frequency of each aspect of error the highest level error found is hypothesized false concepts. So that students still do not fully understand the topic and context discussed in the future tense sentence. Therefore, students must continue to learn to understand the rules of sentence structure and the teacher also develops more teaching methods so that students can easily understand the material.